Summer Palace - Temples of India Project Team (Jio Institute, 2024)
The room is colonnaded and spacious with cusped arches. The entry within the ‘palace’ can be made through two flights of stairs on both ends. The arcade is four-sided with pointed arches. It is also known as the Summer Palace. Small jalis are present on the windows.